Karakteristik Bioadsorben Limbah Ikan dengan Aktivator Kalsium Hidroksida (Ca(OH)2) - Satriawan, Dodi; Anggraeni, Melani; Aghni Bintang Sukono, Geo (Jurnal Teknik Kimia USU, 2025)
This research aims to conduct an initial analysis of the characteristics of bioadsorbent from fish waste which will be used as a pollutant adsorption. Fish waste was obtained from Tempat Pelelangan Ikan (TPI) in Cilacap district, Central Java. The fish waste obtained is dried by drying with solar thermal for 2 – 3 days. The carbonization process of fish waste is carried out by pyrolysis at a temperature of 550 oC for 4 hours until fish waste charcoal is produced. Charcoal is ground to 100 mesh size. The charcoal was then weighed 50 g and activated with 1 L of 5% Ca(OH)2 at a temperature of 70 oC with stirring at 350 rpm for 2 hours; 4 hours; and 6 hours. Analysis of characteristic bioadsorbent refers to SNI 06-3730-1995. Bioadsorbent from fish waste activated at an activation time of 6 hours has the best characteristics in terms of water content and ash content of 2,75% and 20,2% respectively, while the best characteristics in terms of volatile matter content and iodine absorption capacity are found in bioadsorbent without activation of 44,33% and 1.250,46 mg/g respectively.